A study on medication adherence among patients who seek medical care in Hospital Tuanku Ja’afar, Seremban, Negeri Sembilan - Tajudin, Noor Ashikin; Sudardi, Nora Syafiqah (2016)
Background: It is found that patient taking two or more drugs are likely to be non adherence to the medication. This can contribute to health care problems and treatment failure. Thus, this study is conducted to determine the level of medication adherence among patients in Hospital Tuanku Ja’afar, Seremban. Method: The research study was conducted at Hospital Tuanku Ja’afar, Seremban in out-patient setting. All respondents were selected spontaneously as they are at the right time and at the right place. The levels of medication adherence among patients were measured by using 8-Items Morisky Medication Adherence Scale which comprises of eight questions. The scores were calculated and the level of medication adherence were assessed. Results: A total number of 84 (100%) respondents have completed the study. 29 of them (34.5%) reported of having a high level of medication adherence, 12 respondents (14.3%) described of having medium level of medication adherence while the others 43 respondents (51.2%) categorized as having a low level of medication adherence. Descriptive statistics were used to determine the level of medication adherence among respondents and to assess the score obtained from each statement. It found that most of the patients from Hospital Tuanku Ja’afar, Seremban had a low level of medication adherence in their treatment plan due to some common reasons such as difficulty in sticking to the medication therapies, forgetfulness and took the treatment plan lightly. Conclusion: The level of medication adherence among patient are vary depending on their medication taking behaviour. Pharmacists are encouraged to provide appropriate guidelines and information regarding the medication to the patients to obtain the desired therapeutic outcomes. Thus, treatment failure and medication cost can be reduced.